Integration of intermittent renewable power supply using grid-connected vehicles: A 2030 case study for California and Germany - David Dallinger; Gerda Schubert; Martin Wietschel (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2012)
This paper describes a method to characterize the fluctuating electricity generation of renewable energy sources (RES) in a power system and compares the different parameters for California and Germany. Based on this method describing the fluctuation and residual load, the potential contribution of grid-connected vehicles to balancing generation from renewable energy sources is analyzed for a 2030 scenario using the agent-based simulation model PowerACE. The analysis reveals that integrating fluctuating RES is possible with less effort in California because of a higher correlation between RES generation and the load curve here. In addition, RES capacity factors are higher for California and therefore the ratio of installed capacity to peak load is lower. Germany, on the other hand, faces extreme residual load changes between periods with and without supply from RES. In both power system scenarios, grid-connected vehicles play an important role in reducing residual load fluctuation if smart charging is used. Uncontrolled charging or static time-of-use tariffs do not significantly improve the grid integration of RES.
urn:nbn:de:0011-n-2034841
Keywords: 330